Structure of finite nondispersible groups each nonmetacyclic subgroup of which is normal - Kovalenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We determine the structure of finite minimal nondispersible groups each nonmetacyclic subgroup of which is normal (Theorem 2) and describe all finite nondispersible groups each nonmetacyclic subgroup of which is normal (Theorem 3).